The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/etm.2017.5209
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide and its analogues: A review of the potential for immunomodulation of fibrosis diseases and opthalmopathy (Review)

Abstract: Abstract. The US Food and Drug Administration approved thalidomide and its analogues for the treatment of erythema nodosum leprosum, in spite of the notoriety of reports of severe birth defects in the middle of the last century. As immunomodulatory drugs, thalidomide and its analogues have been used to effectively treat various diseases. In the present review, preclinical data about the effects of thalidomide and its analogues on the immune system are integrated, including the effects of cytokines on transdiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…With an improved understanding of the mechanisms of action of thalidomide, it was found to have immunomodulatory, anti-inflammatory, antiangiogenesis and cell proliferation inhibitory properties suitable for treating various diseases. [295][296][297][298] Notably, thalidomide in combination with dexamethasone was approved by the FDA for treating multiple myeloma in 2006. 299 Further studies have indicated thalidomide has marked anticancer activity in various cancers by mediating angiogenesis.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…With an improved understanding of the mechanisms of action of thalidomide, it was found to have immunomodulatory, anti-inflammatory, antiangiogenesis and cell proliferation inhibitory properties suitable for treating various diseases. [295][296][297][298] Notably, thalidomide in combination with dexamethasone was approved by the FDA for treating multiple myeloma in 2006. 299 Further studies have indicated thalidomide has marked anticancer activity in various cancers by mediating angiogenesis.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…(B) FDA approval of IMiDs (Aragon-Ching et al, 2007; FDA and CDER, 2014; Fala, 2015; Ríos-Tamayo et al, 2017). (C) Preclinical studies using IMiDs (Sampaio et al, 1991; Corral et al, 1996; Zhu et al, 2003; Baratz et al, 2015; Wang et al, 2016b; Decourt et al, 2017; Liu T. et al, 2017; Rubenstein et al, 2018).…”
Section: History and Mechanism Of Thalidomide (Figure 2)mentioning
confidence: 99%
“…Thalidomide, an immunomodulatory, anti-fibrotic and anti-inflammatory drug, has previously been indicated by the US FDA for the treatment of erythema nodosum leprosum, systemic lupus erythematous, inflammatory bowel disease, cystic fibrosis, heart failure and several malignant anomalies ( 67 ). The anti-viral activity of thalidomide has been reported, leading to a surge in cellular immunity, i.e.…”
Section: Treatment Strategiesmentioning
confidence: 99%